Linguistic Prefabrication A Discourse Analysis Approach - Ding, Jianxin (Springer Singapore, 2018)
This book presents an innovative exploration of linguistic prefabrication in the travel advertising discourse from a functional perspective. Most of the previous studies on prefabricated language have adopted a structural, systematic point of view. This study, however, aims at exploring its functions in discourse. The material examined here is the discourse of travel advertising, which has become one of the candidates for 'late modern discourse par excellence' and rarely been discussed before. The study covers a wide range of topics, essentially attempting to model linguistic idiomaticity in Systemic Functional Grammar. It assesses how the two fundamental principles of language use, the 'idiom principle' and the 'open-choice principle', interact with each other to construct English texts. As a counterweight to the traditional structural approach to collocations and idiomatic expressions, this study investigates the 'phraseology' of the register of travel advertising, and explores prefabrication and conventionalization in language use and human behavior. It seeks to answer the age-old question of whether human beings are 'primarily like buses, which travel along regular routes' or 'like taxis, which move about freely'. Ritualization, as sociological and anthropological theory have long since recognized, is simply characteristic of all aspects of human behavior and its contexts. .